Morphometric analysis of surface changes in XP-endo group files after root canal instrumentation - A. V. Mitronin; D. A. Ostanina; Yu. A. Mitronin (Эндодонтия Today)
Aim. In the last decades, the field of Endodontics has seen a number of developments. In particular, the creation of the nickel-titanium MaxWire alloy with two fundamental prosperities such as superelasticity and shape memory allow to FKG Dentaire SA to create a completely new generation of instruments. This study aimed to investigate the surface changes of XP-Endo Shaper, XP-Endo Finisher and XP-Endo Finisher R files before and after several uses in vivo as well as after they were immersed in irrigation solutions and sterilization procedures.Material and methods. A total of 18 instruments were used, which were divided into 3 main groups (n = 6). Root canals of 45 extracted mandibular molars were selected and instrumented according to the traditional protocol. The instruments’ surface changes were analysed by scanning electron microscopy (SEM) and X-ray energy-dispersive spectroscopy (EDS).Results. Morphometric changes such as the presence of machining grooves, plastic deformation, microcracks, craters, disruption of the cutting edges and fracture could be visualized by SEM on instruments’ surfaces and EDS revealed the existence of Ni, Ti, Si, O. XP-endo Finisher/R groups showed significant deteriorations after the third use. XP-endo Shaper files exhibited a statistically higher number of surface deteriorations after the fifth use (P < 0.05). It appears that XP-endo group files have a high margin of working capacity and durability as they keep effectiveness up to the third time they have been used. In addition to nickel and titanium, other compounds are present in the elemental composition of these instruments, which can have an impact on the increased strength and endurance of the instruments.